PLASTIC DEFORMATION OF WADSLEYITE: I. HIGH-PRESSURE DEFORMATION IN COMPRESSION - Thurel E.; Cordier P. (My University, 2003)
We have studied the plastic deformation of Mg2SiO4 wadsleyite polycrystals. Wadsleyite was synthesized from a forsterite powder in a multianvil apparatus. It was then recovered and placed in a second multianvil assembly designed to induce plastic deformation by compression between two hard alumina pistons. After the deformation experiment, the microstructures are characterized by transmission electron microscopy (TEM) and large-angle convergent beam electron diffraction (LACBED). Deformation experiments have been carried out at 15-19 GPa and at temperatures ranging from room temperature to 1800-2000 °C. Five different dislocation types have been identified by LACBED: [100], 1/2<111>, [010], <101> and [001]. The [001] dislocations result from dislocation reactions and not from activation of a slip system. The [010] dislocations are activated under high stresses at the beginning of the experiments and further relax by decomposition into 1/2<111> dislocations or by dissociation into four 1/4[010] partial dislocations. The following slip systems have been identified: 1/2<111>{101}, [100](010), [100](001), [100]{011}, [100]{021}, [010](001), [010]{101} and <101>(010).
Keywords: PLASTIC DEFORMATION; DISLOCATION; SLIP SYSTEM; HIGH PRESSURE; TEM